Inhibition of cholinesterase by essential oil from food plant - Chaiyana W. (2014)
Inhibition of cholinesterase has attracted much attention recently because of its potential for the treatment of Alzheimer's disease. In this work, the anticholinesterase activities of plant oils were investigated using Ellman's colorimetric method. The results indicate that essential oils obtained from Melissa officinalis leaf and Citrus aurantifolia leaf showed high acetylcholinesterase and butyrylcholinesterase co-inhibitory activities. C. aurantifolia leaf oil revealed in this study has an IC 50 value on acetylcholinesterase and butyrylcholinesterase of 139 ± 35 and 42 ± 5 μg/ml, respectively. GC/MS analysis revealed that the major constituents of C. aurantifolia leaf oil are monoterpenoids including limonene, l-camphor, citronellol, o-cymene and 1,8-cineole. © 2012 Elsevier GmbH. All rights reserved.